Metallic materials properties development and standardization (MMPDS) : scientific report - Rice, Richard C. (National Technical Information Service [distributor], 2003)
The 2003 Metallic Material Properties Development and Standardization (MMPDS) Handbook is the replacement document for MILHDBK- 5. It is recognized internationally as a reliable source of aircraft materials data for aerospace materials selection and analysis. Consistent and reliable methods are used to collect, analyze, and present statistically based material and fastener allowable properties. Contains extensive information and data for other material properties and characteristics, such as fracture toughness, fatigue, creep strength, rupture strength, fatigue-crack propagation rate, and resistance to stress corrosion cracking.